CONTRACEPTIVE PREFERENCES AND IMPROVED QUALITY OF LIFE - Baqai, Shehla; Siraj, Asifa; Urooj, Uzma; Noor, Nusrat; Tariq, Humaira; Khan, Sumaira (Pakistan Armed Forces Medical Journal, 2021)
Objective: To understand the contraceptive preferences of women of reproductive age group and to know from where they get the knowledge of it and how quality of life of contraceptive users and non-users is affected. Study Design: Cross-sectional study. Place and Duration of Study: Gynecology and Obstetrics department, Pak-Emirates Military Hospital Rawalpindi, from Sep 2017 to Aug 2018. Methodology: Pre-tested self-administered questionnaires were used to assess the usage of contraception, role of health care providers social/family influences, and print/broadcast media, to provide sample size calculation, ethics approval, knowledge and access to various contraceptive methods. The quality of life indicators used were anemia and feeling of general well-being. Results: A total of 1050 participated in the study. Out of those who have knowledge, only 497 (47.33%) practiced contraception and 530 (50.47%) not using it 23 (2.1%) were not clear about their views regarding contraceptive usage. Out of those who were using contraception, 161 (54.20%) women used barrier methods, 93 (18.71%) used intrauterine contraceptive devices, implanon 52 (10.46%), natural methods 61 (12.27%), oral/injectable 99 (19.91%) and male contraception was used by 31 (6.23%) couples. Anemia was less in contraceptive users 84 (17%) as compared to non-users 164 (31%). Conclusion: Family planning is the strongest tool which can improve the health of mother and children as well as it’s a development indicator for overall social and economic status of a society. By understanding its prevalence and factors influencing its usage, maternal and child health can be improved in near future.